Assessment of Consumers Loyalty and Switching Behavior: A Study on Selected Tea Brands in Bangladesh - Shams, Shahpar (Philosophy and Progress, 2016)
Rivalry has become more drastic among diverse companies since it is the era of global marketing now. In order to grasp the best opportunity from the marketplace, marketers now-a-days adopt multifarious strategies to ensure their triumph in the long run. To do so, building and maintaining customer loyalty has become the best option for marketers. Tea marketers in Bangladesh, likewise marketers of other consumer goods, have been facing fierce competition as demand for this drink has been increased. As such, they have also been adopting this technique to ensure their sustainable growth and market holdings. Here, bringing down consumers expectation and perception in the single point is a great challenge for a marketer which is prerequisite to customer satisfaction. In this study, the researcher attempted to work out with attributes those consumers expect in a branded tea and presence of which might create consumers positive perception towards the brand and how this positive perception works for turning to be loyal. In addition to, when positive perception does not work, how consumers switch to other brand for meeting up their expectations. In this context, the researcher has collected direct data from the consumers to understand their views. Philosophy and Progress, Vol#55-56; No#1-2; Jan-Dec 2014